Left ventricular hypertrophy are associated with increased ostial pulmonary vein diameter (Faculty of Medicine Universitas Indonesia, 2006)
Atrial fibrillation (AF), which is called as a global epidemic disease, frequently found in hypertensive patients with left ventricular hypertrophy (LVH). Pulmonary vein (PV), which is known to have an important role in AF initiation and maintenance, increases in its diameter during AF. We sought to investigate PVs diameter changes in LVH with sinus rhythm. Of 70 hypertensive patients with sinus rhythm, 42 subjects demonstrated LVH. The mean ostial diameter of patient with and without LVH, assessed by doing spiral multisliced CT scan in the axial plane, were as follow: right superior (RSPV) of 19.6±2.78 vs 17.8±1.93 (p = 0.003), right inferior (RIPV) of 18.4±3.12 vs 16.0±2.19 (p < 0.001), left superior (LSPV) of 18.1±2.62 vs 16.0±2.16 (p < 0.001), and left inferior (LIPV) of 15.9±1.93 vs 15.4±1.85 mm (p = 0.284), respectively. Even during sinus rhythm, LVH causes PV dilation. This result might give an explanation of frequent AF prevalence in hypertensive patients. (Med J Indones 2006; 15:173-6) Keywords: Pulmonary veins, Left ventricular hypertrophy